Invasive Cytotrophoblasts Manifest Evidence of Oxidative Stress in Preeclampsia - Many, Ariel (American Society for Investigative Pathology, 2000)
In preeclampsia, poor placental perfusion may result in maternal endothelial dysfunction, but the pathways involved are largely unknown. Candidate placental mediators include products of oxidative stress released into the maternal circulation. Xanthine oxidase has been implicated in postischemic-reperfusion injury via the generation of superoxide anion radicals (superoxide; O(2)(.−)) and hydrogen peroxide. We examined placentas and placental bed curettings and/or biopsies from preeclamptic control pregnant women to test the hypothesis that xanthine oxidase is a mediator of oxidative stress in placentas from women with preeclampsia. The expression of xanthine dehydrogenase/xanthine oxidase holoenzyme and the activity of xanthine oxidase, the isoform known to generate reactive oxygen species, were increased in a subpopulation of cytotrophoblasts of preeclamptic women. Additionally, the expression of superoxide dismutase, which would scavenge superoxide produced by xanthine oxidase, was reduced in the same cells. Furthermore, fluorescence immunostaining for nitrotyrosine, which was suggestive of superoxide-nitric oxide interactions to form peroxynitrite anion (ONOO(−)) in vivo, was increased in these cells and in villous vessels. Thus, our data indicate an increased capacity of placental cells to generate reactive oxygen species in preeclampsia.